Right Atrial Fluorodeoxyglucose Uptake Is a Risk Factor for Stroke and Improves Prediction of Stroke Above the CHA2DS2-VASc Score in Patients With Atrial Fibrillation - Wang, Bing; Xu, Yiduo; Wan, Peng; Shao, Shan; Zhang, Feifei; Shao, Xiaoliang; Wang, Jianfeng; Wang, Yuetao (Frontiers in Cardiovascular Medicine, 2022)
Background: Atrial fibrillation (AF) is a common arrhythmia, and its most severe and dreaded complication is stroke. We aimed to explore the relationship between atrial FDG uptake and stroke and whether atrial FDG uptake could provide incremental value above the CHA2DS2-VAS score to predict stroke in AF by 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT). Methods: From September 2017 to December 2020, we retrospectively enrolled 230 patients (115 with AF and 115 without AF) who underwent 18F-FDG PET/CT due to tumor screening or preoperative staging after prolonged fasting. And follow up for at least 12 months, the endpoint event is the occurrence of stroke. We analyzed 18F-FDG uptake in right and left atria (RA/LA), right and left atrial appendage (RAA/LAA) and collected clinical features. In addition, all enrolled population were divided into stroke group and non-stroke group, and relevant clinical features and atrial FDG uptake of the two groups were analyzed. Univariate and multivariate logistic regression analyses were conducted to explore the risk factors of stroke. Receiver-operator characteristic (ROC) curves were performed to examine the discriminatory power of atrial FDG uptake in predicting stroke, and determine whether the addition of atrial FDG uptake improves predictive value beyond the CHA2DS2-VASc score for stroke. Results: More than half of patients with AF had RA FDG uptake and one fifth had LA FDG uptake. The maximum standardized uptake value (SUVmax) of RA and LA in the AF group were significantly higher than that of the non-AF group (all P < 0.001). We followed up the patients for 28 ± 10 months, and finally 31 patients had stroke. Multivariate logistic regression analyses demonstrated that RA SUVmax was the only independent risk factor for stroke (OR = 1.925, 95%CI 1.074-3.451, P = 0.028). Addition of high RA SUVmax to the CHA2DS2-VASc score could predict stroke more effectively, with a larger AUC 0. 790 (P < 0.001). Conclusions: This study found a significant correlation between atrial FDG uptake and AF, especially in RA. RA FDG uptake is a risk factor for stroke, and improves prediction of stroke above the CHA2DS2-VASc score in patients with AF.